LINGUOPRAGMATIC POTENTIAL OF USING AGONAL STRATEGY OF APPEAL TO THE MEDIA (ON THE MATERIAL OF D. TRUMP'S SPEECHES FOR 2020) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-37-47Abstract. The article examines the characteristics of the strategy of appealing to the media, on the basis of Donald Trump's campaign speeches from 2020. It discusses the role of agonistic rhetoric and speech manipulation as key elements of political discourse. The main means of implementing this implied strategy include tactics of opposition, elevating loyal media, condemnation, and interpreting “biased” information. An analysis is conducted of the complex lexical and semantic tools that facilitate the verbalization of these established speech tactics.Key words: political discourse, manipulation, presidential campaign discourse, agonism, media appeal strategy, rhetorical tactics